ISO standards in the concept of quality management of travel companies of Ukraine - Baiev, Vadim; Bakhov, Ivan; Mirzodaeva, Tetiana; Kharchenko, Olena; Hopkalo, Larysa (My University, 2021)
The article considers the system of forming a quality management system of a travel company based on ISO standards and proposes a model of quality management system based on a process approach, using elements of integrated management; a procedure for forming the quality management system of a travel company and a typical organizational structure of the quality management system of a tour operator.

У статті розглянуто систему формування системи управління якістю туристичної фірми на основі стандартів ISO та запропоновано модель системи управління якістю на основі процесного підходу, з використанням елементів інтегрованого менеджменту; порядок формування системи управління якістю туристичної фірми та типову організаційну структуру системи управління якістю туроператора.
Keywords: ISO tourism; sustainable development; tourism services; кафедра туристичного та готельного бізнесу; сталий розвиток; туристичні послуги; інновації (туризм)